Chromium oxide nanoparticles in‐situ immobilized onto nitrogen‐doped carbon plates with boosted catalytic activity toward nitrogen reduction reaction - Wang, Jing; Tang, Chenbo; Liufu, Hui; Zeng, Xia; Huang, Ziyi; Ma, Lin; Li, Hanjia; Chen, Yajie; Sun, Jinyi (Canadian journal of chemical engineering, 2025)
A chromium oxide‐based nanocomposite (Cr 2 O 3 @NC) is designed and prepared via a simple pyrolysis route with Cr‐based metal organic framework (MOF) as a template. The research results indicate that Cr 2 O 3 nanoparticles have an average size of ~70 nm and are in situ formed and imbedded onto the Cr‐based MOF‐derived 2D N‐doped carbon microplates. When employed as an inexpensive electrocatalyst for nitrogen reduction reaction (NRR) to synthesize ammonia, Cr 2 O 3 @NC demonstrates an improved and stable catalytic activity in comparison with bare Cr 2 O 3 . A large ammonia production rate of 29.42 μg mg −1 cat h −1 under a lower potential of −0.4 V versus reversible hydrogen electrode (RHE) can be acquired with a Faradic efficiency of 9.89% in sodium sulphate solution. Additionally, a satisfactory selectivity can also be achieved without hydrazine byproduct. The greatly promoted catalytic activity of Cr 2 O 3 @NC is regarded to be concerned with its desirable structures such as 2D planar topological structure with expanded active surface area, abundant catalytic sites, and effective combination with conductive carbon.